Silo mentality in bureaucratic reform - Surono, Eldest Armyrianti (Economic Military and Geographically Business Review, 2024)
Background: This article discusses how to overcome silo mentality in bureaucratic reform in an organisation. Method: The qualitative research method is based on case studies and literature reviews. This method involves a critical and in-depth evaluation of previous research to understand sectoral ego and silo mentality in organizational contexts, including government and corporate settings. Findings: There are several things that can be done, one of which is by implementing a better mental revolution based on the values of Pancasila which is the basic ideology of the Indonesian nation. Sectoral ego and silo mentality have the potential to be counterproductive to the strategy of achieving organisational targets and goals. Nonetheless, in the preparation of organisational plans and strategies, it has become customary that organisations set performance targets for each unit derived from the organisation's main targets and objectives. It is an interesting discussion considering that each person or organisational unit always tries and focuses on the respective performance targets that have been set. Conclusion: In some conditions, the choice to focus on their own performance targets is one of the reasons why people exhibit sectoral ego behaviour with silo mentality. By revolutionising the mentality as a strong foundation, it is expected that an organisation can achieve the organisational goals that have been set. Novelty/Originality of this study: This study integrates Pancasila values ​​into strategies to overcome the silo mentality in bureaucratic reform. This innovative approach offers practical solutions to align individual performance with organizational goals, applicable in the Indonesian government and private sectors.